Unraveling The Mysteries of Impacted Canines: A Comprehensive Review of Case Report - Panthee, Anuja; Sharma, Apechhya; Bishowkarma, Sharmila (Journal of College of Medical Sciences-Nepal, 2025)
Background Canines are the corner teeth, often known as “fangs” or “eye” teeth. In certain individuals, canine teeth may not fully emerge into a functional position, referred to as impacted canines. Impacted canines present a common yet intricate challenge in dental practice, warranting a nuanced understanding of their etiology, diagnosis and management. This abstract delves into the intricate world of impacted canines, shedding light on their diverse causal factors, ranging from genetic predispositions to environmental influences. Diagnostic strategies, including clinical assessments and imaging modalities, are crucial for the accurate identification and classification of impacted canines. The maxillary and mandibular impacted canine is a frequently encountered clinical problem and diagnosed during the routine dental examination which usually requires an interdisciplinary approach for management. Early detection, timely management, and appropriate surgical and orthodontic intervention can lead to esthetically and functionally acceptable outcomes. Depending on the difficulty and expected outcome, either surgical exposure or extraction of the impacted tooth is performed, followed by complex orthodontic treatment to align the tooth properly within the dental arch. This case report details the surgical extraction of impacted canines in situations where the prognosis is unfavorable.